CEOs’ Financial Background and Non-financial Enterprises’ Shadow Banking Business - Chen Yang; Weitao Shen (Frontiers in Psychology, 2022)
In recent years, the “financial-like” behavior of non-financial enterprises has contributed to the “off real to virtual,” which has seriously restricted the virtuous cycle of finance and economy. This study selects non-financial enterprises listed on Chinese A-shares from 2008 to 2019 as the research sample, and empirically analyzes the impact of CEOs’ financial background (FB) on the shadow banking business of non-financial enterprises and its mechanism. The results show that: (1) CEOs’ FB has a positive effect on shadow banking business of non-financial enterprises; among which, the positive effect generated by non-banking FB is stronger. The conclusions still hold after robustness tests by replacing the measurement of variables, controlling for other shocks, changing the parameter estimation method, and considering the endogeneity problem. (2) The mechanism analysis reveals the positive effect mainly by reducing the level of entity investment by enterprises. (3) The heterogeneity analysis finds that, on the one hand, with respect to the internal micro characteristics of enterprises, the positive effect is more significant in state-owned enterprises, non-manufacturing enterprises, and non-growth stage enterprises. On the other hand, with respect to the external macro environment, the positive effect is more significant in periods of easy monetary policy, in industries with a higher competition or in regions with a better institutional environment. This study reveals the intrinsic mechanism of CEOs’ FB and non-financial enterprises’ shadow banking business, enriches the study of the influencing factors of non-financial enterprises’ shadow banking business, and provides micro-level empirical support to alleviate the “off real to virtual” of the economy.